Creative surrender: How we grow at the end of life. Issue 4 (5th December 2018) - Rake‐Marona, Jennifer
Abstract: Through patients' stories and reflection on the literature, the author explores the potential for spiritual, emotional, and relational growth in the dying. Five "faces" of growth are described: Holy Sadness, Meaning‐Making, Generosity of Spirit and Transcendence, Legacy and Eternal Life, and Letting Go. Readers are invited to consider the creative potential at the end of life and to be aware that they too may grow as they journey alongside others who are approaching death.